PERAN SUAMI DAN KELUARGA TERHADAP PEMBERIAN ASI EKSLUSIF PADA IBU YANG BEKERJA, MENYUSUI DAN MEMILIKI BAYI DIATAS 7 BULAN - ORISINAL, ORISINAL; YASNI , HILMA; FATHIMI, FATHIMI; JUMADEWI, ASRI (CENDEKIA: Jurnal Ilmu Pengetahuan, 2024)
The growth of the golden period of newborns really needs nutritional intake obtained from breast milk. Existing data shows that the prevalence of exclusive ASI by mothers to their children is very low, this is influenced by various factors such as the reasons for mothers who work as career women, problems with breast milk production with insufficient production, women with modern lifestyles, health problems, easy access to formula milk and family readiness to provide support to breastfeeding mothers. The purpose of the study was to obtain an overview of information support, assessment support, and emotional support for working mothers in readiness to provide full breast milk without complementary foods for 6 consecutive months (exclusive breastfeeding). The location of the study was in Samadua Village, South Aceh in 2023, this study was explanatory research with an accidental sampling technique obtained as many as 57 mothers with inclusion criteria being breastfeeding mothers, career mothers (working) and having babies 7-12 months. Primary data collection through questionnaires (direct interviews) on mothers who met the inclusion criteria. Statistical tests were used to analyze the results of the data obtained descriptively and analysis of the relationship between variables with the chi square test and multiple logistic regression statistical tests. The results of the study obtained in the form of information support as much as 14% are dominated by the role of the husband. While the distribution of forms of support from husbands and family members is categorized as less good in all support, both information support (78.9%), assessment (75.4%) and emotional support (70.2%). The results of statistical tests with a p-value <0.05 concluded that there was an influence of assessment and emotional support that influenced mothers towards exclusive ASI. ABSTRAKPertumbuhan masa-masa emas bayi baru lahir sangat memerlukan asupan nutrisi yang diperoleh dari ASI. Data yang telah ada menunjukkan prevalensi ASI eksklusif oleh ibu kepada anaknya sangat rendah, hal ini dipengaruhi berbagai faktor seperti alasan ibu yang bekerja sebagai wanita karier, masalah ASI dengan produksi yang kurang, wanita dengan gaya hidup modern, masalah kesehatan, mudahnya mendapat susu formula dan kesiapan keluarga untuk memberikan dukungan kepada ibu menyusui. Tujuan penelitian untuk memperoleh gambaran dukungan informasi, dukungan penilaian, dan dukungan emosional pada ibu yang bekerja dalam kesiapan memberikan full ASI tanpa makanan pendamping selama 6 bulan berturut-turut (ASI eksklusif). Lokasi penelitian di gampong Samadua Aceh Selatan tahun 2023, penelitian ini bersifat explanatory research dengan teknik sampel secara accidental sampling yang diperoleh sebanyak 57 orang ibu dengan kriteria inklusi adalah ibu yang menyusui, ibu karier (bekerja) dan mempunyai bayi 7-12 bulan. Pengambilan data secara primer melalui kuesioner (wawancara secara langsung) pada ibu yang memenuhi syarat kriteria inklusi. Uji statistik dipakai untuk menganalisis hasil data yang diperoleh secara deskriptif dan analisis keterkaitan antar variabel dengan uji chi square dan uji statistik regresi logistik berganda. Hasil penelitian yang diperoleh berupa dukungan informasi sebanyak 14% adalah didominasi oleh peran suami. Sedangkan distribusi bentuk dukungan suami dan anggota keluarga masuk kategori kurang baik pada semua dukungan, baik dukungan informasi (78,9%), penilaian (75,4%) dan dukungan emosional (70,2%). Hasil uji statistik dengan nilai p-value <0.05 menyimpulkan adanya pengaruh dukungan penilaian dan emosional yang memengaruhi ibu terhadap pemberian ASI ekslusif.